Understanding the Grails 3 domain model - Kousen, Ken; Safari eBooks ([Place of publication not identified] : O'Reilly, 2017)
"In this video course, expert Java trainer and consultant Ken Kousen shows you how to build a simple Grails 3 application, starting with installation options, IDE usage, and learning how Grails handles HTTP requests and responses. He provides a quick primer on how to use the Groovy programming language to work comfortably in Grails before creating a new project from the Grails Application Forge. From there, he dives into the underlying architecture of a Grails 3 application, which includes adding controllers, seeing how responses are returned and rendered, and unit testing controllers."--Resource description page.
Presenter, Ken Kousen.
Title from title screen (viewed May 11, 2017).
Keywords: Grails (Computer file); Groovy (Computer program language); Web site development; Application software -- Development; Open source software; Electronic books